Chelerythrine induces apoptosis via ROS‐mediated endoplasmic reticulum stress and STAT3 pathways in human renal cell carcinoma. Issue 1 (30th September 2019) - He, Hongchao; Zhuo, Ran; Dai, Jun; Wang, Xiaojing; Huang, Xin; Wang, Haofei; Xu, Danfeng
Abstract: Renal cell carcinoma (RCC) is a heterogeneous histological disease and it is one of the most common kidney cancer. The treatment of RCC has been improved for the past few years, but its mortality still remains high. Chelerythrine (CHE) is a natural benzo[c]phenanthridine alkaloid and a widely used broad‐range protein kinase C inhibitor which has anti‐cancer effect on various types of human cancer cells. However, its effect on RCC has not been fully elucidated. In this study, we evaluated the effect and mechanism of CHE on RCC cells. Our study showed that CHE induced colony formation inhibition and G2/M cell cycle arrest in a dose‐dependent manner in RCC cells. In addition, CHE increased cellular ROS level, leading to endoplasmic reticulum (ER) stress, inactivating STAT3 activities and inducing apoptosis in RCC cells which were suppressed by NAC, a special ROS inhibitor. We further found that both knockdown of ATF4 protein and overexpression of STAT3 protein could reduce CHE‐induced apoptosis in Caki cells. These results demonstrated that the apoptosis induced by CHE was mediated by ROS‐caused ER stress and STAT3 inactivation. Collectively, our studies provided support for CHE as a potential new therapeutic agent for the management of RCC.